Effectiveness Cross Selling Marketing to Increase Number Customers Easy Mudharabah Savings Products - Nurwidya Astuti; Arin Setiyowati; Fatkur Huda (LAA MAISYIR : Jurnal Ekonomi Islam, 2025)
A development of the Islamic banking industry demands an effective marketing strategy to reach and retain customers. One of the strategies implemented cross selling, which was combined with the Prize Party Program. This research aimed to examine the effectiveness of this strategy in increasing the number of Easy Mudharabah Savings customers at BSI KCP Rungkut 1 Surabaya. This research used a qualitative approach of case studies, with in-depth interview techniques and observations of the two main informants in September 2024. The data analysis was carried out through reduction, presentation, and drawing conclusions with data validity through source triangulation. The result showed that the implementation of the cross selling strategy combined with the Prize Party incentive program proved to be effective. It was shown by the achievement of daily targets and a success rate of around 90%, especially from Easy Mudharabah products. However, the obstacles were found such as limited visual promotion and incompatibility of product features with customer needs. This research contributed through a direct evaluation of reward-based marketing strategies in the context of Islamic banking.